Research on Air Conditioning Electrical Energy Saving Control Based on Computer Neural Network. Issue 2 (August 2021) - Li, Mingjun; Wu, Qing; Chen, Deming
Abstract: Air conditioning has become an indispensable electrical equipment in people's life. However, there are still a considerable number of air conditioning electrical equipment control is still mainly based on conventional control, these control methods have great limitations, which makes its energy saving effect is greatly affected. Based on this, this paper first analyses the energy-saving principle of air-conditioning system, then studies the energy-saving control of air-conditioning system based on neural network, and finally gives the evaluation strategy of air-conditioning electrical energy-saving based on nerve network.